Teletrabalho e home office: vantagens e desvantagens decorrentes da (re)organização do trabalho imposta pela pandemia COVID-19 - Faria, Rayra Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This paper aims to analyze the ways of implementing telework and home office and its intensification in the context of the COVID-19 pandemic, in order to highlight the advantages and disadvantages of these labor relations for workers and employers. Understanding the contours of labor organizations, as well as researching the economic, psychosocial and labor impacts of the implementation of new virtual labor relations, are essential in a pandemic context. Therefore, it starts from the investigation about the legislation and the doctrinal position about the alteration of the work organizations, emphasized by the social isolation. This academic production permeates data collection, with the adoption of bibliographical research in published materials about the characteristics of telework and home office. In addition, the method of approach, the deductive, allows the investigation of the economic, social and labor consequences for workers and employers. It is intended, then, to follow the legislative evolution (or lack thereof) of the telework modality, the international scenario on the subject and the consequent flexibility that the COVID-19 pandemic causes in the labor regime, emphasized mainly by the MP 927 and 936 and ADI 6342 and 6362.

O presente trabalho tem por objetivo analisar as formas de implementação do teletrabalho e home office e sua intensificação no contexto da pandemia COVID-19, de modo a evidenciar as vantagens e desvantagens dessas relações laborais para trabalhadores e empregadores. Entender os contornos das organizações laborais, bem como pesquisar os impactos econômicos, psicossociais e laborais da implementação de novas relações trabalhistas virtuais tornam-se essenciais em um contexto pandêmico. Parte-se, para tanto, da investigação acerca da legislação e o posicionamento doutrinário acerca da alteração das organizações laborais, enfatizados pelo isolamento social. Esta produção acadêmica perpassa a coleta de dados, com a adoção da pesquisa bibliográfica em materiais publicados sobre os nuances características do teletrabalho e home office. Além disso, o método de abordagem, o dedutivo, permite a averiguação das consequências econômicas, sociais e laborais para os trabalhadores e empregadores. Pretende-se, então, acompanhar a evolução legislativa (ou a falta dela) da modalidade do teletrabalho, o cenário internacional sobre o tema e a consequente flexibilização que a pandemia COVID-19 causa no regime trabalhista, enfatizadas, principalmente, pelas Medidas Provisórias nº 927 e nº 936 e as Ações Diretas de Inconstitucionalidade 6342 e 6362.
Teleworking and home office: advantages and disadvantages arising from the (re)organization of work imposed by the COVID-19 pandemic
Keywords: Labour Law; flexibility; flexicurity; fundamental rights and guarantees; Direito do Trabalho; flexibilização; flexissegurança; garantias fundamentais do cidadão